1994
DOI: 10.1172/jci117445
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ionic consequences of dietary salt loading in essential hypertension. Relation to blood pressure and effects of calcium channel blockade.

Abstract: To study the ionic basis of salt sensitivity in hypertension, Tl_-, 31p-, and 'Na-nuclear magnetic resonance techniques were used to measure cytosolic free calcium (Ca1), pH (pH,), free magnesium (Mg1), and sodium (Na4) in erythrocytes of essential hypertensive subjects (n = 19). Individuals were studied for 2 mo each on low-(UNaV < 50 meq/d) and high-(UNaV > 200 meq/d) salt diets, with the concomitant administration of nifedipine (10 mg t i.d.) or placebo tablets for 1 mo of each diet. Salt loading elevated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
3
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 44 publications
4
31
3
1
Order By: Relevance
“…Our basal [Ca 2ϩ ] i level probably reflects improved methods with minimal activation of platelets and correction for dye leakage from platelets. Recent data from careful investigations of methods have shown basal [Ca 2ϩ ] i in human platelets as low as the level determined in our study (6,11,17,27).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our basal [Ca 2ϩ ] i level probably reflects improved methods with minimal activation of platelets and correction for dye leakage from platelets. Recent data from careful investigations of methods have shown basal [Ca 2ϩ ] i in human platelets as low as the level determined in our study (6,11,17,27).…”
Section: Discussioncontrasting
confidence: 54%
“…Resnick et al (26,27) previously described a decrease in intraerythrocyte concentration of free Mg 2ϩ in essential hypertension based on studies employing nuclear magnetic resonance spectroscopy. Results contrary to ours may be due to differences in the cells used for [Mg 2ϩ ] i measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous report we showed that lymphocyte Na + -H + exchange is elevated in hypertensive patients 12 and a number of previous studies have confirmed elevated Ca cyt in red cells from hypertensive patients. 9,26 It is not clear what mechanism(s) mediate the in vitro phenomenon of elevated red cell SLC activity or increased Ca cyt in hypertensive patients. However, elevated SLC activity is not only present in patients with essential hypertension but also in patients with diabetic nephropathy and is a predictor of progression to microalbuminuria in nondiabetics.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, SLC activity may be affected by other intracellular processes such as protein kinase C (PKC) 7 and cell calcium. 8 In this regard, increased cell calcium is present in red blood cells, platelets and lymphocytes from hypertensive patients [9][10][11][12] and has a multimodal distribution in hypertensives. 12 Cell calcium may also be modulated by insulin 13 and increased intracellular calcium has been associated with insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nifedipine consistently elevated intracellular pH values (23). An enhanced activity of the H + -Na + antiporter (as a major mechanism of cell defense against cellular acidification) has been reported in lymphocytes (24) as well as in the renal brush border membrane of spontaneously hypertensive rats (25) and in hypertensive rats (26).…”
Section: Discussionmentioning
confidence: 87%